Ecomorphological evolution of South-American Colubroidea snakes (Squamata: Serpentes) - Ferreira, Gabriel Spanghero Vicente (2020)
This dissertation explored ecomorphological patterns in South American Colubrid snakes, testing for associations between body shape and ecological parameters. Comparative phylogenetic tools were used to answer macroevolutionary questions related to body shape evolution in colubrid snakes that differ in microhabitat usage and activity period. Major assumptions presume associations between form (morphology) and function (locomotion and thermoregulation in different environmental settings), premises corroborated by previous functional studies using live snakes. The dissertation comprises two chapters that used morphological measurements obtained in 61 species of snakes from the Colubridae and Dipsadidae families and ecological information available in the literature. The first chapter rescued evidence of functional morphology related to locomotion on different habitat structures already proposed by other studies to support predictions of convergent patterns on slenderness and tail length associated with different degrees of arboreality in Colubroidea. We compared patterns of slenderness and tail length patterns to evaluate if both traits evolved under similar environmental pressures related to arboreality. To test our predictions, we constructed a dataset of morphological measurements - snout vent length (SVL), mid-body circumference (MBC) and tail length - and another dataset of ecological information (index of arboreality). Associations between relative mid-body circumference (a proxy of slenderness) and relative tail length with different degrees of arboreality were tested using two comparative phylogenetic tools: 1) phylogenetic generalized least square (PGLS) and 2) evolutionary models fitting. The morphological evolution of the group included specialization in the use of arboreal microhabitats associated with an increase in body elongation, however, highly slenderer arboreal species did not necessarily exhibit longer tails. We proposed that, even if both characteristics evolved in association with the arboreal lifestyle in general, tail length is apparently similar among species that occupies any degree of arboreal substrate, while slenderness possibly evolved associated with the frequency of time spent in arboreal substrate. The second chapter rescued the theory of heat exchange dynamics related to variation in body shape to investigate associations between Surface Area to Volume ratio (S/V) and differential use of thermal environments. We aimed to investigate if species that explore similar thermal environments (derived from similar microhabitats), such as fossorial, terrestrial and arboreal, or that are active at similar diel periods (diurnal or nocturnal) evolved similar Surface Area to Volume ratio, which likely differs from that observed among species that explore dissimilar microhabitats or diverge in the activity period. We constructed one morphological dataset and an ecological data base for each species. Methods used in applied stereology and geometry were imported here to compile the morphological data of S/V, and available information from literature was used to construct the ecological data base. Ecomorphological associations between S/V and different ecological categories were tested using PGLS and phylogenetic ANOVAs. No differences in S/V patterns were identified between species that use distinct microhabitats or differ in activity periods. Possibly, snakes have developed physiological and behavioral traits that allow them to explore a variety of different thermal environments. In agreement with previous studies, this study indicates that snakes in general did not evolved specific morphological patterns associated with thermal variables.